Case Report: Pengaruh Edukasi Menyusui terhadap Produksi Asi dalam Program Asi Ekslusif di NICU RSUD DR.Tjitrowardojo Purworejo - Nofita Kurniawati; Falasifah Ani Yuniarti; Rina Perawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Introduction: Mother's milk (ASI) is a very good nutritional intake for newborn babies. Natural breast milk produced by mothers has important nutrients for babies. Breast milk contains various microbial materials. Nutrition for mothers who are breastfeeding must be given optimally. Oxytocin massage is a non-pharmacological technique that functions to overcome substandard breast milk production. Objective: This study aims to determine the effect of breastfeeding education on breast milk production. Method: This research uses a descriptive observational method using a case study method approach. The subject used was a postpartum mother patient with breast milk production problems in the NICU room at Dr. Tjitrowardojo Hospital, Puroworejo. Data collection was carried out by interviewing Mrs. V and also looked at the medical records in the PICU/NICU room using the neonate assessment format developed by the UMY FKIK Nurse Professional Education. Results: After being given intervention for 5 days, there was an effect of breastfeeding education on breast milk production. Conclusion: Breastfeeding education can influence breast milk production.